Prevalence of psychological violence in the employed Brazilian population and its occurrence in the workplace: National Survey of Health 2019 - Priscila Maria Stolses Bergamo Francisco; Daniela de Assumpção; Marcia Bandini; Sergio Roberto de Lucca (Revista Brasileira de Epidemiologia)
ABSTRACT Objective To estimate the prevalence of psychological violence among employed adults aged 18-69 years; to verify the distribution of sociodemographic and lifestyle characteristics within those who have reported psychological violence in the workplace; and to estimate the number of individuals who have reported this type of violence perpetrated by the employer/boss in the workplace. Methods: This is a descriptive study with data from the National Survey of Health (2019). Employed people were selected in relation to the workforce. Psychological violence was defined as follows: in the last 12 months, “has anyone offended, humiliated, or mocked you in front of other people?”. For those who reported violence, the location of the incident and who the aggressor was were verified. The prevalence of psychological violence was estimated and the characteristics of those who suffered this type of violence were described by absolute and relative frequencies. Results: The prevalence of psychological violence reached 11% (95% confidence interval [CI]: 10.5–11.6) of the employed adult population, was higher among women, individuals between 18–29 years old, Black people, single, and among those with income up to 0.5 minimum wage. Of the individuals who suffered psychological violence in the workplace, 57.6% were men, 31.9% were between 30–39 years old, 47% were mixed-race, 44.4% completed high school, 39.8% had an income between one and two minimum wages, 13.5% were smokers, 37.6% consumed alcoholic beverages, and 23.8% consumed alcohol excessively. As for the aggressor, 28.8% (around two million people) reported that psychological violence in the workplace was committed by the employer/boss. Conclusion: According to the study results, among the employed Brazilian population, 11% reported psychological violence in the last year; we identified the segments most affected by psychological violence in the workplace and measured this violence having the boss/employer as the aggressor.